Antiadherent AgBDC Metal-Organic Framework Coating for Escherichia coli Biofilm Inhibition - Ana Arenas-Vivo; Vanessa Celis Arias; Georgiana Amariei; Roberto Rosal; Isabel Izquierdo-Barba; Tania Hidalgo; María Vallet-Regí; Hiram I. Beltrán; Sandra Loera-Serna; Patricia Horcajada (MDPI AG, 2023)
Surface microbial colonization and its potential biofilm formation are currently a major unsolved problem, causing almost 75% of human infectious diseases. Pathogenic biofilms are capable of surviving high antibiotic doses, resulting in inefficient treatments and, subsequently, raised infection prevalence rates. Antibacterial coatings have become a promising strategy against the biofilm formation in biomedical devices due to their biocidal activity without compromising the bulk material. Here, we propose for the first time a silver-based metal-organic framework (MOF; here denoted AgBDC) showing original antifouling properties able to suppress not only the initial bacterial adhesion, but also the potential surface contamination. Firstly, the AgBDC stability (colloidal, structural and chemical) was confirmed under bacteria culture conditions by using agar diffusion and colony counting assays, evidencing its biocide effect against the challenging E. coli, one of the main representative indicators of Gram-negative resistance bacteria. Then, this material was shaped as homogeneous spin-coated AgBDC thin film, investigating its antifouling and biocide features using a combination of complementary procedures such as colony counting, optical density or confocal scanning microscopy, which allowed to visualize for the first time the biofilm impact generated by MOFs via a specific fluorochrome, calcofluor.